Translation Analysis of Student’s Work (Study of Poetry Translation) - Syukril Khair; Bambang Suwarno; Arono Arono (Universitas Bengkulu, 2018)
The literary translation still becomes such of debating among several experts and researchers, especially at translation studies. The aim of this study was to find out what kinds of techniques of translation were applied in translating the poems of Maya Angelou, and how the appropriateness of techniques were applied by the students. Mollina & Albir’s classification of translation techniqueswas used as the primary theory in the analysis of the translation texts.This study was descriptive qualitaive and content analysis. The data were taken from text translations of two poems which consist of 550 data from 10 students as translators. The research findings revealed that14 techniques were used by students. The result showed that there were 14 translation techniques which were used, compensation, literal translation, modulation, linguistic amplification, discursive creation, linguistic compression, reduction, amplification, adaptation, transposition, borrowing, established equivalent, particularization, and description. The next finding showed that the appropriate techniques wereapplied at 69.3%. Meanwhile, inappropriate techniques were at 30.7%. The conclusion of this study was that students used the most at compensation and the lowest was description. The students mostly successful in applying appropriate technique at delivering messages, but were flub in recreating thepoetical aspect in Target Language. In some cases, this indicated deficiency in determining the equivalent expression in the target text. The suggestion for further researchers is to explore a similar study by investigating on figurative speech and poetical aspect at poetry translation.